Penyelesaian Soal-Soal Mengerti Fisika : Mekanika, Termofisika, Listrik dan Magnet, Gelombang - SETIAWAN, Sandi (Andi Offset, 1992)
Penyelesaian Soal-Soal Mengerti Fisika : Mekanika, Termofisika, Listrik dan Magnet, Gelombang